South African radiographers' radiation protection practices, a qualitative study. Issue 2 (May 2022) - Lewis, S.; Downing, C.; Hayre, C.M.
Abstract: Introduction: Radiation protection is multifarious, and consequently, a radiographers' application of radiation protection is multifaceted. Studies have shown varying radiation protection practices among radiographers. The first quantitative phase of this explanatory, sequential mixed-method study used the theory of planned behaviour to explore South African radiographers' radiation protection behaviour. Overall, South African radiographers' attitudes to radiation protection, subjective norm, perceived behavioural control, and radiation protection intention was high. This second phase of the study aimed to explore the reasons for South African radiographers' radiation protection practices. Methods: This study used an exploratory and descriptive qualitative approach. Data was collected through 13 in-depth semi-structured telephone interviews. Thematic analysis was used in order to uncover original phenomena. Data saturation was achieved and the study adhered to trustworthiness and ethical measures. Results: Thematic analysis identified two themes. The participants had the appropriate radiation protection knowledge, but radiation protection compliance remained a personal choice. Impediments such as feeling rushed during imaging of trauma and challenging patients, patients knowledge of radiation protection, resources, imaging referrals, inadequate training when transitioning from analogue to digital radiography and managerial support contributed to radiation protection compliance. Strategies such as further education, research and a change in mindset were suggested to further foster radiation protection compliance. Conclusion: Even though participants' knowledge of radiation protection aligned with the legislated guidelines, limited internalising of the knowledge resulted in compliance being a personal choice. Participants reflected on their insouciant attitude and observed a similar attitude in their radiographer colleagues. Patient and work-related impediments were identified to contribute to radiation protection compliance. Strategies to further foster compliance were suggested. Implications for practice: Understanding the reasons for radiographers' choice in radiation protection will allow the development of strategies that foster optimum application of radiation protection practises. Developing a radiation protection culture that enhances personal compliance supported by education and evidence should be considered.